2010
DOI: 10.1097/mop.0b013e32833fde85
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics in pediatric leukemia

Abstract: Purpose of review The therapeutic index of many medications, especially in children, is very narrow with substantial risk for toxicity at doses required for therapeutic effects. This is particularly relevant to cancer chemotherapy, where the risk of toxicity must be balanced against potential suboptimal (low) systemic exposure that can be less effective in patients with the higher rates of drug clearance. The purpose of this review is to discuss genetic factors that lead to interpatient differences in the phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 103 publications
0
30
0
Order By: Relevance
“…90 The case for complete omission of prophylactic cranial irradiation Studies of survivors of childhood ALL have found that prophylactic cranial irradiation can cause many late-occurring sequelae, including second cancers, neurocognitive impairment, and multiple endocrinopathy. 91,92 Recognizing the devastating complications of cranial irradiation, pediatric oncologists have steadily reduced the use of this treatment modality since the late 1970s.…”
Section: Pharmacogenomics-guided Continuation (Maintenance) Treatmentmentioning
confidence: 99%
“…90 The case for complete omission of prophylactic cranial irradiation Studies of survivors of childhood ALL have found that prophylactic cranial irradiation can cause many late-occurring sequelae, including second cancers, neurocognitive impairment, and multiple endocrinopathy. 91,92 Recognizing the devastating complications of cranial irradiation, pediatric oncologists have steadily reduced the use of this treatment modality since the late 1970s.…”
Section: Pharmacogenomics-guided Continuation (Maintenance) Treatmentmentioning
confidence: 99%
“…PEG-asparaginase demonstrates a prolonged half-life and decreased renal excretion relative to the parent compound [15]. In addition, the pegylated formulation increases efficacy and reduces the possibility of antibody generation by preventing reticuloendothelial uptake [16, 17]. The newly developed Erwinia asparaginase produced a lower rate of allergic reaction and has been demonstrated to produce effective asparaginase activity even in patients who had previously experienced an allergy to PEG-asparaginase [18].…”
Section: L-asparaginasementioning
confidence: 99%
“…Since 3–14% of patients are heterozygous for TPMT associated with lower enzyme activity, routine pre-treatment testing is suggested and once identified, these patients should start with a dose reduction in the 6-MP level by 30–70% [53]. Notably, the FDA now recommends testing for the most commonly identified inactive SNP genotype, which can prospectively predict patients at higher risk of developing 6-MP-induced hematopoietic toxicity [16, 49, 50]. It is most useful in ALL protocols containing high doses 6-MP (>50 mg/m 2 /day) [5].…”
Section: -Mercaptopurine (6-mp)mentioning
confidence: 99%
“…Heterozygotes typically need a dose reduction between 35% and 50%, and homozygotes need a dose reduction of about 90%. 3,4 Expression of TPMT does not change significantly during development, 6 allowing use of these suggested dose reductions across the pediatric and adult spectrum. As azathiopurine is a prodrug of 6-MP, its pharmacokinetics involves TPMT, and prospective genotyping is recommended.…”
Section: Oncologic and Immunomodulatory Pharmacotherapymentioning
confidence: 99%